2024
DOI: 10.1097/mjt.0000000000001707
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa–Carbidopa–Entacapone Intestinal Gel in Advanced Parkinson Disease: A Multicenter Real-Life Experience

József Attila Szász,
Adriana Octaviana Dulamea,
Viorelia Adelina Constantin
et al.

Abstract: Background: For Parkinson disease (PD) patients who have been diagnosed with advanced disease that can no longer be effectively controlled with optimized oral or transdermal medications, a range of device-aided therapies (DAT) are available, comprising either deep brain stimulation or infusion therapies providing continuous dopaminergic stimulation. Levodopa–entacapone–carbidopa intestinal gel (LECIG) infusion is the latest DAT for advanced PD (APD) that was approved in Romania in 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…As the experience using LECIG was limited when it became available in our country, we selected for initiation mostly patients who previously also had entacapone therapy. In a recently published retrospective evaluation of 74 APD patients treated with LECIG at 12 specialized APD centers in Romania, we showed that during the titration period as well as the post-PEG adjustment period, we did not encounter any significant adverse effects compared to those mentioned in the literature regarding the PEG insertion procedure [ 56 ]. We would like to point out that in the present evaluation, none of the entacapone-naive patients experienced gastrointestinal adverse effects; furthermore, none of the patients showed modified laboratory results on further testing.…”
Section: Discussionmentioning
confidence: 99%
“…As the experience using LECIG was limited when it became available in our country, we selected for initiation mostly patients who previously also had entacapone therapy. In a recently published retrospective evaluation of 74 APD patients treated with LECIG at 12 specialized APD centers in Romania, we showed that during the titration period as well as the post-PEG adjustment period, we did not encounter any significant adverse effects compared to those mentioned in the literature regarding the PEG insertion procedure [ 56 ]. We would like to point out that in the present evaluation, none of the entacapone-naive patients experienced gastrointestinal adverse effects; furthermore, none of the patients showed modified laboratory results on further testing.…”
Section: Discussionmentioning
confidence: 99%